Editorial. Issue 1 (1st March 2019) - Magonet, Jonathan
Abstract : Gabriel Josipovici first contributed to European Judaism during its third year of publication in the Summer 1968 issue. In his role as Managing Editor, Rabbi Michael Goulston z'l sought to use the journal to provide, among other things, a place for outreach and dialogue between those who represented the religious leadership of the Jewish people, in this case rabbis of his own generation who belonged to 'progressive' movements in the UK, and Jewish 'intellectuals' perceived as being alienated from, indifferent to or somewhat marginal within their own Jewish tradition. Thus, the same issue includes the proceedings of a symposium on 'Judaism and Marxism: The First European Dialogue'.